Studi Alternatif Substrat Kertas untuk Pengujian Viabilitas Benih dengan Metode Uji UKDdp - Faiza Chairan i Suwarno; Indri Hapsari (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
A study to determine the best alternative substrate paper for testing seed viability in rolled paper method was conducted with 2 experiments. The first experiment studied the physical characteristic of six substrate papers, straw, filter, stencil, CD, HVS and Samson related to seed germination. The second experiment was conducted to identify the best alternative substrate for testing germination of different seeds. High and low viability of rice, maize, peanut, yardlong bean, chick pea and leafy vegetable seeds were tested with the substrate papers arranged in a Randomized Block Design with three replications. The first experiment showed that CD and Stencil papers had good physical characters for germination substrate. Water absorption of CD and stencil papers were 28.1g and 24.4g per medium unit, lower than Straw paper (46.51 g/medium unit) but significantly higher than the international standard of filter paper (20.7g/medium unit). In rolled paper test, no significant difference of water holding ability among the papers. Water lost during the 7 day testing were less than 2 g/medium unit for all of the papers. All of the papers including stencil and CD papers were homogenous with low coefficient of variation, less than 5%. The second experiment showed that different data of germination percentages and dry weight of normal seedlings were obtained from the diferrent subtrate papers. As compared to the common substrate straw paper, the stencil paper produced the most similar data, 100% and 91.7% similarities of germination percentage and dry weight of normal seedlings, respectively, whereas the other papers performed 37.5 - 91.6% and 29.1 - 66.7%. Key words: Substrate paper, physical characteristic, seed viability testing.